Portuguese Health System – Challenges in Times of Genomics - Dias Pereira, André Gonçalo (Review of European and Comparative Law, 2024)
This article presents the Portuguese health care system that combines the National Health Service, health subsystems and private health insurance. Genomic medicine is expanding the scope of its activity, and its main challenges in pre-natal medicine and post-natal healthcare will be presented here and it will be discussed whether a private health insurance system can provide genomic medicine. As the Four “Ps” concept of Medicine is increasingly relevant, it is important to check if the private system can accommodate this evolution.